SIFAT KEMAHATAHUAN ALLAH MENURUT KITAB MAZMUR - Lie Agan; Jessi Darius (JURNAL PENABIBLOS, 2024)
God's omniscience is one of God's characteristics in general, but Psalm 139:1-24 explains in detail about God's omniscience, regarding humans as His special creation. This descriptive research using library data sources aims to explain the characteristics of God's omniscience according to Psalm 139:1-24. The results of this research are as follows: First, Allah's omniscience cannot be separated from His other characteristics, namely His eternity. Second, Allah knows all about humans and everything they do. Third, Allah knows all about nature and everything that happens in it. Fourth, Allah is omniscient and sovereign over everything that has happened, is happening and will happen. Fifth, Allah knows all eternity in the past and eternity to come.